Fighting for peace in Somalia a history and analysis of the African Union Mission (AMISOM), 2007-2017 - Williams, Paul 1975- (Oxford University Press, 2018)
Fighting for Peace in Somalia provides the first comprehensive analysis of the African Union Mission in Somalia (AMISOM), an operation deployed in 2007 to stabilize the country and defend its fledgling government from one of the world's deadliest militant organizations, Harakat al-Shabaab.00The book's two parts provide a history of the mission from its genesis in an earlier, failed regional initiative in 2005 up to mid-2017, as well as an analysis of the mission's six most important challenges, namely, logistics, security sector reform, civilian protection, strategic communications, stabilization, and developing a successful exit strategy. These issues are all central to the broader debates about how to design effective peace operations in Africa and beyond
Keywords: African Union Mission in Somalia; Geschichte 2007-2017; National security / Somalia; Peacekeeping forces / Somalia; National security; Peacekeeping forces; Somalia